Investing in strategies to reverse the global incidence of TB - Broekmans, Jaap (Earthscan : UN Millennium Project, Task Force on HIV/AIDS, Malaria, TB, and Access to Essential Medicines, Working Group on TB, 2005)
"This report lays out the recommendations of the UN Millennium Project Working Group on TB. The working group's recommendations include expanding access to DOTS programs, implementing efforts against HIV-related TB and multidrug-resistant TB, engaging all primary care providers and communities in high quality TB care, and developing new diagnostics, drugs, and vaccines. These bold yet practical approaches will enable countries in every region of the world to halve the prevalence of TB by 2015"--Jacket